Essential updates 2019/2020: Surgical treatment of gallbladder cancer. Issue 2 (29th January 2021) - Matsuyama, Ryusei; Yabusita, Yasuhiro; Homma, Yuki; Kumamoto, Takafumi; Endo, Itaru
Abstract: Gallbladder cancer is a biliary tract cancer that originates in the gallbladder and cystic ducts and is recognized worldwide as a refractory cancer with early involvement of the surrounding area because of its anatomical characteristics. Although the number of cases is increasing steadily worldwide, the frequency of this disease remains low, making it difficult to plan large‐scale clinical studies, and there is still much discussion about the indications for surgical resection and the introduction of multidisciplinary treatment. Articles published between 2019 and 2020 were reviewed, focusing mainly on the indications for surgical resection for each tumor stage, the treatment of incidental gallbladder cancer, and current trends in minimally invasive surgery for gallbladder cancer.